2013
DOI: 10.1007/s40258-013-0038-9
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Diagnosis Excess Acute Care Costs in Alzheimer’s Patients among a US Medicaid Population

Abstract: Compared with controls, Medicaid AD patients incurred higher acute care costs in the 12 months prior to their preliminary diagnosis, suggesting room for beneficial interventions and better disease management should earlier diagnosis become possible. These findings may be especially relevant in light of new criteria facilitating earlier diagnosis of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 26 publications
8
51
0
Order By: Relevance
“…Our findings also showed that higher estimated costs in the first two years after diagnosis were preceded by significantly higher unadjusted costs among participants with dementia in the 12 months prior to diagnosis. Studies examining utilization and costs in the period before a dementia diagnosis have reported an increase in most measures of outpatient and inpatient utilization as well as costs beginning in the year prior to diagnosis . Higher costs in the prediagnosis period may result from a higher comorbidity burden among individuals with dementia and the concomitant challenges of managing comorbid conditions in the setting of cognitive impairment .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also showed that higher estimated costs in the first two years after diagnosis were preceded by significantly higher unadjusted costs among participants with dementia in the 12 months prior to diagnosis. Studies examining utilization and costs in the period before a dementia diagnosis have reported an increase in most measures of outpatient and inpatient utilization as well as costs beginning in the year prior to diagnosis . Higher costs in the prediagnosis period may result from a higher comorbidity burden among individuals with dementia and the concomitant challenges of managing comorbid conditions in the setting of cognitive impairment .…”
Section: Discussionmentioning
confidence: 99%
“…People with MCD may utilise more GP services to seek help with symptoms of cognitive decline, but their higher usage may also be due to poorer management of comorbid conditions or having more accidents or injuries [12]. Previous research has hypothesised that the use of GPs may also be affected by participants' living arrangement, income or access to services [10,17].…”
Section: Discussionmentioning
confidence: 99%
“…Older adults with any MCD have more comorbid medical conditions, such as stroke, hypertension, diabetes mellitus [7,8,9] and cerebrovascular disease, than those without any MCD [10]. Mood disorders, such as anxiety or depression, have also been found to be more prevalent in people with cognitive impairment [8,11,12,13]. To prolong living within the community, individuals with cognitive or physical impairments may utilise more health services [5], particularly primary care.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations